Diurnal plasma free fatty acid profiles in normal and diabetic pregnancies. Issue 6088 (10th September 1977) - Gillmer, M D; Beard, R W; Oakley, N W; Brooke, F M; Elphick, M C; Hull, D
Abstract : Diurnal plasma free fatty acid (FFA) and glucose concentrations were measured in 23 normal women, 13 chemical diabetics, and 11 insulin-dependent diabetics in late pregnancy. The mean diurnal FFA value was lowest in the insulin-requiring diabetics and highest in the chemical diabetics. Although no association was found between percentile birthweight and maternal mean fasting or diurnal FFA, there was a positive correlation between percentile birthweight and both mean maternal fasting plasma glucose and mean diurnal glucose in normal and chemical diabetic women. These observations support the view that glucose is the major substrate used by the fetus, but birthweight may be influenced more by the total substrate crossing the placenta than by maternal levels of either glucose or FFA alone.